Cell motility and role of ACTC1 in migration of malignant glioma cells - Wanibuchi, Masahiko (Progress in Neuro-Oncology, 2020)
The cytoskeleton, consisting of actin filaments, intermediate filaments, and microtubules, plays an important role in cellmotility during invasion of carcinomas or sarcomas into neighboring tissues. In malignant gliomas, migration of the tumorcells into the brain parenchyma promotes local and/or distant metastasis. In this article, the mechanism of cell motility isreviewed, focusing on actin, alpha cardiac muscle 1 (ACTC1) which is one of the six isoforms of actin. Actin is present in two different forms in the cytoplasm, a globular monomer, called G-actin, and a linear polymer, called F-actin or actin filament. Actin filaments form networks through cross linkers. They are important for migration of malignant tumor cells, both through mesenchymal and amoeboid modes. The mesenchymal migration involves polymerization of actin filament at the leading edge of the lamellipodia, and by depolymerization of actin filament at the trailing edge, leading to contraction. On the contrary, the amoeboid migration is induced by the formation of a bleb, formed by contraction of actin-myosin complex in the cytoplasm, close to the cell membrane. The protruded bleb leads to migration through the extracellular matrix.In malignant gliomas, the expression of ACTC1 is upregulated. In clinical situation, patients of ACTC1-positive glioblastoma demonstrated invasion of the contralateral cerebral hemisphere at the time of diagnosis, and distant metastasis in the remote areas of the brain at the time of recurrence. Time-lapse study demonstrated that the in vitro motility of glioblastoma cells was significantly inhibited by knockdown of ACTC1.Actin filament-dependent cell motility is also important in migration of gliomas. Among the various isoforms of actin, ACTC1 may serve as a marker for migration in these malignant cells.